1999
DOI: 10.1037/0022-3514.77.4.669
|View full text |Cite
|
Sign up to set email alerts
|

When fair is foul and foul is fair: Reverse priming in automatic evaluation.

Abstract: Responses to information were facilitated by the rapid prior presentation of evaluatively congruent material. This fundamental discovery (R. H. Fazio, D. M. Sanbonmatsu, M. C. Powell, & F. R. Kardes, 1986) marked a breakthrough in research on automatic information processing by demonstrating that evaluative meaning is grasped without conscious control. Experiments employing a word naming task provided stringent tests of the automaticity of evaluation and found support for it. More strikingly, a previously unob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
6
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(258 citation statements)
references
References 52 publications
12
228
6
12
Order By: Relevance
“…This finding is in accordance with results from evaluative priming studies using external stimuli as primes that already reported blunted priming effects in high anxious participants (Berner & Maier, 2004;Glaser & Banaji, 1999;Maier, Berner, & Pekrun, 2003). It is also consistent with previous action-monitoring studies which have…”
Section: Functional Properties Of Automatic Evaluation Of Actionssupporting
confidence: 93%
“…This finding is in accordance with results from evaluative priming studies using external stimuli as primes that already reported blunted priming effects in high anxious participants (Berner & Maier, 2004;Glaser & Banaji, 1999;Maier, Berner, & Pekrun, 2003). It is also consistent with previous action-monitoring studies which have…”
Section: Functional Properties Of Automatic Evaluation Of Actionssupporting
confidence: 93%
“…In other words, while we hypothesized that worry could interfere with the rapid affective tagging of actions selectively, we reckoned that anxious arousal could increase PES specifically, revealing a functional dissociation between these two components of anxiety during action monitoring. Further, because previous studies already found blunted priming effects associated with (trait) anxiety irrespective of action monitoring (Berner & Maier, 2004;Glaser & Banaji, 1999;Maier, Berner, & Pekrun, 2003), we also included a control task in Experiment 1 where a standard cue-target priming sequence (with external stimuli) was used. As external visual primes, we used angry and happy faces extracted from the Karolinska Directed Emotional Faces set (AKDEF; Lundqvist, Flykt & Öhman, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the strength of the consciously experienced visual percept would require some time to become apparent, being dependent on feedback projections. Also, there is evidence from the affective priming literature that automatic effects of stimulus valence are transient (De Houwer, Hermans, & Eelen, 1998;Glaser & Banaji, 1999;Hermans, de Houwer, & Eelen, 1994Klauer, Rossnagel, & Musch, 1997;see Fazio, 2001, for a review). Applying these concepts to the present experiments, the activation of affective valence associated with a famous face was expected to modulate the strength of the visual percept within a range of response latencies, not including very fast or slower latencies.…”
Section: Introductionmentioning
confidence: 99%